Inkonsistensi Perusahaan Industri Komoditas Minyak Kelapa Sawit terhadap Aturan Roundtable On Sustainable Palm Oil (RSPO) Studi kasus : Pelanggaran Kejahatan Lingkungan pada Tahun 2014-2016 oleh Perusahaan Malaysia dan Indonesia Sebagai Anggota RSPO - M.Andhika Yudistira; Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This study aims to determine how the influence of RSPO policy as an IGO that regulates the palm oil industry sustainably against Indonesian and Malaysian companies located in the country of Indonesia precisely in Kalimantan. This research is a descriptive study based on the framework of concept of Transnational Environmental Crime by United Nations Human Environment, International Organization by Boer Mauna, and regime compliance concept by Beth A. Simmons. This research is a qualitative research using library research as a data source. The results obtained are the effectiveness of RSPO regulation as IGO which regulates palm oil industry continuously to see inconsistency from 2014-2016